Analisis Fikih Aktual dan Hipotesis Atas Eksposisi Eksistensi Artificial Intelligence dalam Transaksi - Hidayat, Rahmat (Universitas Muhammadiyah Surabaya, 2021)
This study aims to determine Islamic law on AI (artificial intelligence) in transactions. In this era, AI has entered into various sectors of commerce. Many large companies have used AI in various functions and roles.Â So it is necessary to study the legal impact of AI in transaction. This research uses a normative method with a conceptual approach. In transactions, weak AI has occupied at least three positions out of four possible positions, as objects, tools and limited agent. Meanwhile, strong AI, which occupies a position as an independent entity, does not yet exist at this time. At least three positions can be measured actually and one position can be measured hypothetically. Weak AI as objects, tools and limited agent is punished by rules related to its position. But in general, the blame for the AI in these three positions lies with the provider and not the AI itself. Meanwhile, AI as an independent entity, if it is analogous to the general rules of transactions, then all the consequences of his wrongful actions will be charged to him. Because the error is the result of the ability of think independently. The punishment that can be applied is punishment within the scope of ta'zir that is adjusted to government regulations as well as scientific research on the limits of AI intelligence.